The Effect of Independence and Competence on Audit Quality at the BPKP Representative of North Sumatra Province - Fachruddin, Wan; Sari, Eka Puspa; Saraswati, Dwi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
This study aims to determine the effect of: (1) Independence on Audit Quality, (2) Competence on Audit Quality, and (3) Independence and Competence on Audit Quality. Research is causal research. The sample in this study were 33 auditors who worked in the IPP, PPE, AN and P3APIP fields at the BPKP Representative of North Sumatra Province. The research sample was determined by purposive sampling method. This research questionnaire was measured using a Likert scale. Data analysis using multiple linear regression analysis with data quality test, classical assumption test, and data hypothesis testing with the help of SPSS 26 software. The results of this study indicate that (1) Independence has no effect on Audit Quality. This is indicated by the Sig value. 0.0775> 0.05 and the value of t count 1.832 < t table 2.04227. (2) Competence affects Audit Quality. This is indicated by the Sig value. 0.000 <0.05 and the t value is 5.229> t table 2.04227. (3) Independence and Competence simultaneously affect Audit Quality. This is indicated by a value of 0.000 <0.05 and an F value of 26.409> F table 3.32.